Third-harmonic generation enhancement in polymer-dispersed liquid crystal grating - Wicharn, S.; Buranasiri, P. (My University, 2014)
In this paper, the enhancement of third-harmonic generation in one-dimensional periodic grating structure with lowindex contrast, which is produced by holographic illuminated liquid crystal droplets and called polymer-dispersed liquid crystal grating, with near-infrared pumping has been demonstrated. The observed enhancement process is theoretically explained and modeled with a multi-scale perturbation analysis and split-step Fourier transform technique, respectively. We show that the third-harmonic generation has been enhanced by setting the fundamental frequency wavelength to the long-wavelength band-edge of the first photonic band-gap of this periodic structure and satisfying band-edge phasematched condition. The numerical results show that a dramatic enhancement of the third-harmonic field is observed near the long-wavelength band-edge of the second photonic band-gap. Furthermore, the conversion efficiency of thirdharmonic field of forward-propagating direction is more than of backward-propagating direction by a factor of 600.
Keywords: band-edge phase-matching; multi-scale perturbation analysis; one-dimensional photonic crystal; polymer-dispersed liquid crystal grating; third-harmonic generation